Characteristics of red sorgum flour ice cream cones (Sorghum bicolor L) and seaweed puree (Eucheuma cottonii): Karakteristik cone es krim tepung sorgum merah (Sorghum bicolor L) dan puree rumput laut (Eucheuma cottonii) - Latifa Jihan Kusumawati; Vivi Nuraini; Akhmad Mustofa (Agrobiotek, 2025)
Cone is a type of biscuit in wafer qualification that is cone-shaped and used as an ice cream holder. Cone is usually made from wheat flour with the addition of other ingredients as supporting ingredients. Research on making ice cream cones is still rarely done, especially making ice cream cones using red sorghum flour and Eucheuma cottonii puree. This study aims to determine the chemical, physical, and organoleptic characteristics of ice cream cones that are high in fiber and protein, and preferred by consumers. The research used a two-factor factorial completely randomized design (CRD), namely the ratio of wheat flour: red sorghum flour ((90:10), (80:20), (70:30)) and the addition of Eucheuma cottonii seaweed puree/100ml water (5%, 10%, 15%). The results showed that the best treatment was found in the treatment of the ratio of wheat flour: red sorghum flour (80: 20) and the percentage of Eucheuma cottonii puree 10% with fiber content of 4.14% and protein content of 9.73% and organoleptic tests with the results of color 3.53 (neutral), taste 4.23 (like), aroma 3.83 (neutral-like), texture 3.63 (neutral-like), overall liking 4.20 (like). Red sorghum flour ice cream cone and seaweed puree (Eucheuma cottonii) can provide an alternative in increasing food products that are high in protein and fiber.